Effortful Control, Attention and Executive Functioning in the Context of Autism Spectrum Disorder - Page, Teneille (Department of Psychology, 2019)
Autism Spectrum Disorder (ASD) involves a broad presentation of symptoms classified along continuum of severity, with core deficits in Social Affect and Restricted, Repetitive Behaviours required for formal diagnosis (American Psychiatric Association, 2013; Lauritsen, 2013). The development of particular cognitive, behavioural and interpersonal difficulties seen in ASD is of great interest. Temperament offers particular value given that it influences the development of social behaviours, emotionality and self-regulation (Shiner et al., 2012). The self-regulatory temperament factor, effortful control, is known to be diminished in ASD (Garon et al., 2009, 2016) and is theorised to be related to attention and executive functioning (Rothbart & Rueda, 2005). This link is of particular interest, given that attention and executive function deficits are prominent in ASD (Craig et al., 2016; Lai et al., 2017; Sanders, Johnson, Garavan, Gill, & Gallagher, 2008). To date, however, a thorough literature search failed to yield a study which has investigated whether effortful control,attention and executive functioning are concurrently associated with ASD symptomatology.Moreover, the relationship between effortful control, attention and executive functioning is not as unambiguous as previously theorised in typical development, with little investigation into these relationships in ASD. To elucidate the association effortful control, attention and executive functioning have with ASD symptomatology, the relationship between effortful control and these cognitive variable needs to be better established empirically. Therefore the current investigation’s aims were twofold. Study One investigated the relationship of effortful control with attention and executive functions in neurotypical and ASD samples. Study Two explored the association between effortful control, attention, executive functions and core ASD deficits (i.e. Social Affect and Restricted, Repetitive Behaviours). A sample of 38 ASD and 38 neurotypical boys (aggregate-matched on key demographic factors), aged 6 - 15, and their primary caregivers were recruited. Study One considered both groups (n=76) and featured both quasi-experimental and relational investigations. Study Two focused only on the ASD sample (n=38) and used a purely relational design. Neurocognitive measures were used to assess two attention domains (i.e. attention span and sustained attention), and three executive functions (i.e. working memory, inhibition and switching). Effortful control was measured using a parent-report questionnaire and ASD core deficits were examined using the Autism Diagnostic Observation Schedule, Second edition (ADOS-2; Lord, Luyster, Gotham, & Guthrie, 2012). Results of Study One revealed effortful control was a significant predictor of attention span, working memory and inhibition, with ASD participants performing significantly more poorly on these cognitive domains and rated significantly more poorly on effortful control. Study Two’s results indicated that Social Affect was significantly correlated with inhibition and the interaction effect between effortful control and working memory. Furthermore, only effortful control, attention span and their interaction effect were significantly associated with Restricted Repetitive Behaviours. Specifically, effortful control was found to moderate this relationship. At high levels of effortful control, increased attention span was associated with less Restricted, Repetitive Behaviours. These findings may aid efforts to establish a predictive model for ASD core deficits on the basis of temperament and cognitive difficulties. Keywords: Autism Spectrum Disorder (ASD), Effortful Control, Attention, Executive Functions, Social Affect, Restricted Repetitive Behaviours